(untitled) (International journal of medical sciences, 2026)
Pulpitis is a common dental condition that requires prompt and effective treatment to prevent further complications such as tooth loss. The aim of this article is to explore the modern methods available for treating pulpitis, with a focus on recent advancements in endodontics. Emphasis is placed on minimally invasive procedures, biocompatible materials, laser therapy, and regenerative endodontic techniques. These innovative approaches aim to improve the success rates of pulpitis treatment by enhancing the preservation of dental pulp vitality and reducing the need for extensive dental procedures. The article also discusses the role of advanced diagnostic tools, such as digital radiography and cone-beam computed tomography (CBCT), in detecting pulpitis early and planning the most effective treatment strategies.